(untitled) (University of Khartoum Engineering Journal, 2022)
Theories of soil mechanics and basic hydraulic relations and principles of loose boundary channel hydraulics were combined and integrated to analyze stratified river bank failure due to undercutting (undermining) of a bottom loose layer. A near bank velocity distribution model was developed from which the boundary shear stress acting on the bank surface was determined. The model allows computation of the eroded soil volume from the bottom loose layer and the lateral undercut distance at any time in the flow hydrograph as long as the induced flow shear stress is greater than the particle critical shear stress resistance to hydraulic entrainment. At failure the size of the failure block and the ultimate critical value of the lateral undercut distance are determined. Therefore the annual rate of bank retreat and bank sediment load contribution can be identified for the reach under consideration. The application of the model to the River Nile hydrograph in Northern Sudan State showed a good agreement with field observations.